Effect of dietary boron on learning and behavior in rats administered with boric acid - Ozdemir, Hulya; Yaren, Biljana; Oto, Gokhan (Cellular and Molecular Biology, 2019)
This study was designed to investigate the effect of dietary boron on spatial learning, anxiety, some vitamins and oxidative parameters in rats. Thirty-two Wistar albino male rats were used in the study. The rats were equally divided into four groups with 8 rats each: I control group: standard pellet diet only, II. group: 250 ppm boric acid, III. group: 500 ppm boric acid and IV. group: 1000 ppm boric acid added into standard pellet diet. Over a five-week period, elevated plus-maze test was used for anxiety assessment and Morris water maze test was used for evaluating spatial learning. Additionally, blood samples were obtained at the end of the experiment and were used to determine the serum levels of some vitamins and oxidative parameters. Dietary boron significantly increased weight gain (p<0.001) and food consumption in the 250 ppm and 500 ppm groups (p<0.05). Although boron supplementation had no significant effect on learning and anxiety-related behavior, it had beneficiary effects on memory retention in the 1000 ppm group (p<0.05). Biochemical analyses showed a significant decrease in the MDA levels (p<0.05) and an increase in vitamin D3 levels (p<0.01) in the 500 ppm group, a significant increase in GSH-Px activity in the 250 ppm and 500 ppm groups (p<0.05), and a decrease in vitamin E levels in all the experimental groups (p<0.05). In conclusion, our study demonstrated that dietary boron can be beneficial for health when administered at appropriate doses.